Bulgaria : 2007 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bulgaria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007 Article IV Consultation highlights that Bulgaria's large external imbalance has continued to widen. Driven by massive capital inflows, particularly foreign direct investment inflows, the current account deficit could reach a record level of 20 percent of GDP in 2007. Although the present level of the current account deficit is clearly above sustainable levels, external competitiveness has remained adequate. Bank credit has again started to expand rapidly after the administrative credit limits imposed during 2005-06 lapsed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet